INTERNALISASI NILAI TASAMUH DALAM PEMBINAAN KARAKTER SANTRI DI PONDOK MBURI WONG BODHO MBORO MENGANTI GRESIK - Sofyan Maulana; Ali Ahmad Yenuri (Journal Multicultural of Islamic Education, 2022)
Pondok Mburi Wong Bodho is a rehabilitation cottage and also accommodates all people who experience problems in their lives, Gus Khoiri is the caretaker of Pondok Mburi Wong Bodho who directly guides the students with advice and activities which encourage goodness. The principle that is built in the cottage is "Golek Oh Pengweaan" the students are required to look for activities that are useful for themselves in this case the students are always given direct direction by Gus Khoiri with direct guidance so the students will slowly find the character in him each. The research used in this study is qualitative, the design used is phenomenology, the techniques applied are field notes, interview transcripts , and documentation and empirical data that have been obtained, in carrying out data techniques the researchers took data by observation, interviews and also documentation about Pondok Mburi wong Bodho. From the results of the study, it can be concluded that the process of internalizing the value of tasamuh in character building through daily activities, the results of the formulation: weekly activities and annual activities, in carrying out the approach the caregiver uses an approach by understanding the nature, character and character of students, the results of the formulation. The values formed include the value of sincerity, the value of mutual respect, the value of mutual cooperation, the value of honesty, the value of togetherness and the value of mutual respect for differences.